(untitled) (Revista Apotheke, 2024)
In 2020, the project “Art History as a Ghost Story for adults” was carried out at Instituto Federal Catarinense, on the campus Ibirama, with high school students. The objective of the project was to teach Art History, firstly from chronologically grouped artistic movements, then to question this formatting through the production of image montages, inspired by Aby Warburg’s Mnemosyne Atlas, learning concepts such as Pathosformel, Nachleben and ghost-image. This text analyzes four of the boards produced by the students, related especially to Pathosformel, according to the heritage of this important German historian, showing the power of the image to expand the repertoire, sensitivity and ability to think visually in young students through knowledge through image montage.